Cutaneous vaccination ameliorates Zika virus-induced neuro-ocular pathology via reduction of anti-ganglioside antibodies. Issue 9 (1st September 2020) - Beaver, Jacob T.; Mills, Lisa K.; Swieboda, Dominika; Lelutiu, Nadia; Esser, Edward S.; Antao, Olivia Q.; Scountzou, Eugenia; Williams, Dahnide T.; Papaioannou, Nikolaos; Littauer, Elizabeth Q.; Romanyuk, Andrey; Compans, Richard W.; et al.
ABSTRACT: Zika virus (ZIKV) causes moderate to severe neuro-ocular sequelae, with symptoms ranging from conjunctivitis to Guillain-Barré Syndrome (GBS). Despite the international threat ZIKV poses, no licensed vaccine exists. As ZIKV and DENV are closely related, antibodies against one virus have demonstrated the ability to enhance the other. To examine if vaccination can confer robust, long-term protection against ZIKV, preventing neuro-ocular pathology and long-term inflammation in immune-privileged compartments, BALB/c mice received two doses of unadjuvanted inactivated whole ZIKV vaccine (ZVIP) intramuscularly (IM) or cutaneously with dissolving microneedle patches (MNP). MNP immunization induced significantly higher B and T cell responses compared to IM vaccination, resulting in increased antibody titers with greater avidity for ZPIV as well as increased numbers of IFN-γ, TNF-α, IL- and IL-4 secreting T cells. When compared to IM vaccination, antibodies generated by cutaneous vaccination demonstrated greater neutralization activity, increased cross-reactivity with Asian and African lineage ZIKV strains (PRVABC59, FLR, and MR766) and Dengue virus (DENV) serotypes, limited ADE, and lower reactivity to GBS-associated gangliosides. MNP vaccination effectively controlled viremia and inflammation, preventing neuro-ocular pathology. Conversely, IM vaccination exacerbated ocular pathology, resulting in uncontrolled, long-term inflammation. Importantly, neuro-ocular pathology correlated with anti-ganglioside antibodies implicated in demyelination and GBS. This study highlights the importance of longevity studies in ZIKV immunization, and the need of exploring alternative vaccination platforms to improve the quality of vaccine-induced immune responses.